Potential Seed Source for the Preservation of Bitti (Vitex cofassus) in the Community Forest of Burau District, South Sulawesi, Indonesia - Yumna Yumna; Witno Witno; Nardy Noerman Najib; Liana Liana; Ikmal Ikmal (Universitas Panji Sakti, 2023)
Bitti (Vitex cofassus) is one of the most important tree species in Sulawesi, or in some areas, it is also known as gofasa. Bitti wood is also widely used for other uses, such as building timber and carpentry wood. This study aimed to determine the potential source of beetroot (Vitex cofassus) seeds in the Community Forest of Burau Village. This study used the exploratory method by making plots using purposive sampling on a 100m x 100m plot with 38 sampling plots.. Data analysis of potential beetroot seed sources includes measuring diameter, tree height, tillering potential, and determining scoring based on the presence of seeds to determine the possibility of Bitti tree seeds. The results of this study showed that the phenotypic characteristics of the 18 plots that had been selected were a total diameter of 524.44, an entire tree height of 272 m, and a branch-free height of 50.5 m of the 18 parent trees that have been identified, then selected with the criteria of having fruit and saplings. Bitti trees have the most significant tillering potential, found in plot 21 with 0.005% of tillers and 0.0097% of the fruit. Other results obtained the highest value in the parent tree with a score of 73 with a potential class of 5. Genetic and environmental factors can affect plant growth, so the selection of seed source trees to get Bitti mother plants with good phenotypic quality will produce quality seeds.